Who says? content analysis of online mainstream media reportage of COVID-19 "medical" claims made by Philippine public officials (March 2020-March 2022) - Delfin, Rommel De Mateo 2000; Fajardo, Freyzelle Kate Vinan 2000.; Lambino, Marichu C. (Quezon City College of Mass Communication, University of the Philippines, 2023)
This study analyzes the coverage by Philippine online mainstream media of public officials who made statements regarding COVID-19 "medical" claims using the Integrated Framework for Online News Quality Assurance which evaluates online news quality and assessment of the development of developed interventions to counter creation, spread and consequences of misinformation and disinformation. The study is geared toward analyzing Philippines online media's reportage of politicians' (president, spokesperson, state lawmakers, governor, mayor) COVID-19 claims and myths and determining the gap in the media 's supposed intervention in the pieces of disinformation. The researchers would look at the reportage of six prominent COVID cure claims from six politicians from varied positions in the government in the period of trhe pandemic.

In a pandemic where online media sources emerge as key players for COVID-19 prevention and vaccine information, interventions such as fact-checking of alarmist spins, claims and myths should be appropriately executed to avoid costly, harmful and fatal impacts. Responsible and timely corrections of claims especially those that are coming from reputable and newsworthy sources should be the norm. instead of merely amplifications coming first to be published. Through a qualitative conceptual content analysis, the researchers would determine concepts of online media's intervention on disinformation pieces from public officials by analyzing how these information agents assure the quality of news they create using the intervention mechanisms suitable for the quality issues of their activities.
Vita.
Thesis
Includes bibliographical information (pages 51-56) and appendices (pages 56-171).
Keywords: COVID-19 Pandemic, 2020- , in mass media; COVID-19 (Disease) -- Philippines; Press -- Philippines; Misinformation -- Philippines; Disinformation -- Philippines